Magnesium Fertilizer Increased Growth, Rhizome Yield, and Essential Oil Content of Ginger (Zingiber officinale) in Organic Field - Sardiana, I Ketut; Kusmiyarti, Tati Budi; Roni, Ni Gusti Ketut (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2022)
Ginger (Zingiber officinale) is the main biopharmaceutical export commodity of Indonesia. However, its productivity and quality are low because it is not cultivated using optimal techniques. This study aimed to examine the effect of magnesium (Mg) fertilizer on the growth, rhizome yield, and essential oil content of two ginger varieties in the organic field. The two factors tested were the rate of Mg fertilizer application (0, 50, 100, and 150 kg MgOha-1) and the variety of ginger (elephant ginger [Zingiber officinale var. officinarum] and red ginger [Zingiber officinale var. rubrum]). The variables measured were plant height, number of leaves, number of tillers, rhizome weight, and essential oil content. Mg fertilizer application rate and ginger variety significantly affected growth, yield, and essential oil content. No interaction effects were found between the two factors. Mg fertilizer applied at 150 kg MgOha-1 resulted in the highest rhizome yield and essential oil content, with an increase of 21.74% and 15.38%, respectively, compared to the control (0 kg MgOha-1). The yield of elephant ginger was 29.41% higher than that of red ginger, whereas the essential oil content of the red ginger was 16.67% higher than that of the elephant ginger.